Implementation of the International Code of Marketing of Breast-milk Substitutes and maternity protection: correlations with commercial milk formula consumption in East Asia and the Pacific - Ching, Constance; Nguyen, Tuan T.; Pereira-Kotze, Catherine; Zambrano, Paul; Baker, Phillip; Mathisen, Roger (Frontiers in Pediatrics, 2025)
ObjectiveThe rise of commercial milk formulas (CMF) consumption by infants and young children raises concerns about their health, development, and survival. Implementing the International Code of Marketing of Breast-milk Substitutes (the Code) and maternity protection policies are two of seven critical policy actions to protect breastfeeding. This study explores the implementation of the Code, maternity protection policies, and CMF consumption in 11 countries in the East Asia Pacific (EAP) region and determines whether there are any correlations.MethodsData on CMF consumption (from 2006 to 2019 with the projection to 2024 at the global, regional, and national levels), Code implementation scores and the age range covered by national measures, and maternity protection policies were used. Simple linear regressions were conducted to explore correlations between CMF consumption and Code implementation as well as maternity protection.FindingsIn 2019, EAP contributed to 63% of global CMF consumption, toddler formula was the highest category, a product that is unnecessary and unsuitable for consumption by young children. Sales volumes and per capita consumption of most CMF types have increased in the region between 2006 and 2024. Currently, nine out of the 11 countries have adopted Code legal measures. Japan and Malaysia have none and are relying on voluntary measures. Australia, New Zealand, and Singapore now have some Code provisions as legal measures (none in 2020). CMF marketing in Australia and New Zealand remain largely voluntary. Only the Philippines and Thailand are covering CMF up to 36 months. Seven of the 11 countries provide the minimum maternity protection entitlements based on International Labour Organization (ILO) standards. As total scores on Code implementation increased, per capita CMF consumption decreased. Most countries with high overall CMF consumption had no Code legal measures. Philippines, with the highest Code implementation score, showed the lowest per capita CMF consumption. Though no correlation found between CMF consumption and paid maternity leave duration, other forms of maternity protection were not included in the regression.RecommendationAdopt legal measures to give full effect to the Code as opposed to relying on voluntary measures. Prioritise strengthening comprehensive maternity protection, cultivate intersectoral policy environments.